Kepribadian Menurut Tokoh Tasawuf Abu Hamid Muhammad - Fitriah, Lailatul; Apriliani, Wella Ayu (Prodi Tasawuf dan Psikoterapi Fakultas Usluhuddin dan Dakwah IAIN Kediri, 2021)
The emergence of many schools of personality in modern psychology is a representation of current human efforts scientifically to understand his own personality as a whole. The concept of personality in Islam should be a normative reference for Muslims. The personality of a Muslim should not be assessed from the point of view of personality theory from the west, because both of them have different perspectives in understanding and also assessing reality. Abu Hamid also proposed the concept of human beings, namely al-nafs, al-qulb, al-ruh, al-aql. Where these four elements form the personality of the human being. The psychological dimension according to Abu Hamid Muhamad consists of: (1) physical dimension, namely the biological dimension; (2) the vegetable dimension, is the material component of the individual self that can be damaged. He is a passive object that has no power without outside engineering; (3) the animal dimension, this dimension consists of two forces, namely driving force and catching power.